The Strategies and Problems in Film Title Translation - Kudirka, Robertas; Juzelėnienė, Saulė; Lazauskaitė, Laima (Respectus Philologicus, 2016)
The translation of fictional work is not simply a substitution of source language characters with the target language signs, but rather a complex phenomenon, related to many social, cultural and communication components, rendering the transformation of worldview. It is also applied to the translation of films and their titles, viewed as indexing signs, related to the content of what might be expected. The complexity of title translation might be compared to the translation of advertisings, commercials or logos. The article aims at discussing the specifics of translation strategies related to the translation of film titles, covering the period from 1990–2010. The study reveals that the strategies of addition, omission, creation, preservation, transference, deletion, localization and transformation were noticable. It was also noted that in order to achieve persuasion, the strategies of transformation, omission and addition can be applied. The modifications of the ST in the film title translation are directly related to the pragmatic strategies of persuasive discourse.